Advances in biological and medical physics. - Lawrence, John H. (John Hundale), 1904-1991; Hamilton, Joseph G. (Joseph Gilbert), 1907- (Academic Press, 1951)
Advances in Biological and Medical Physics, Volume II highlights the application of nuclear physics to biological and medical problems. This volume is composed of nine chapters, and start with survey on the biological effects of radiation exposure. The succeeding chapters deal with the mechanisms of molecular exchange and blood transfusion; the use of carbon isotopes in in vivo and in vitro animal studies; and the principles and applications of radioautographic technique. These topics are followed by discussions on the carcinogenic potential of ionizing radiation and the detection or measure.